The Wiener-Hopf Method in Electromagnetics - Daniele, Vito G. (The Institution of Engineering and Technology, 1753)
The Wiener-Hopf Method in Electromagnetics is an advanced academic book which provides a rare comprehensive treatment of the Wiener-Hopf method. Using a high level mathematical approach to complex electromagnetics problems and applications, this new book illustrates the wide range of the latest applications, including an extensive outline of the most powerful analytical tool for the solution of diffraction problems.
Description based upon print version of record.
Keywords: Electromagnetism -- Mathematics.; Wiener-Hopf equations.; Electromagnetic waves -- Diffraction -- Mathematics.; elektronické knihy; electronic books